Nanocomposites of poly(l-lactide) and surface-modified chitin whiskers with improved mechanical properties and cytocompatibility. (August 2016) - Li, Cairong; Liu, Hua; Luo, Binghong; Wen, Wei; He, Liumin; Liu, Mingxian; Zhou, Changren
Graphical abstract: Highlights: The CHWs were prepared and further surface modified with PLLA to obtain g -CHWs. The g -CHWs can disperse more uniformly in PLLA matrix than CHWs. The interfacial adhesion between g -CHWs and PLLA matrix was obviously improved. Tensile property of g -CHW/PLLA nanocomposite is superior to PLLA and CHW/PLLA. The addition of g -CHWs to PLLA can obviously improve cell adhesion and growth. Abstract: Rod-like chitin whiskers (CHWs) were prepared by acid hydrolysis and then surface-modified with l -lactide to obtain grafted CHWs ( g -CHWs). The structures, morphologies and properties of the CHWs and g -CHWs were studied by FTIR, solid state 13 C NMR, TG, XRD, FESEM and TEM. Subsequently, CHWs and g -CHWs were used as reinforcing agents for a poly( l -lactide) (PLLA) matrix to fabricate CHW/PLLA and g -CHW/PLLA nanocomposites via solution casting. The resulting nanocomposites were fully characterized in terms of crystallization behavior, thermal transitions, morphology, mechanical properties and cytocompatibility. The nucleating effect of the CHWs and g -CHWs was confirmed by POM and DSC analysis, and as a result, the degree of crystallinity of PLLA in the CHW/PLLA and g -CHW/PLLA nanocomposites was higher than that of neat PLLA. FESEM and TEM observations indicated that g -CHWs were better dispersed throughout the matrix than CHWs due to the surface-modifications of the whiskers. Correspondingly, using an optimized g -CHW content of 5 wt%, the tensile strength, tensile modulus and fracture energy of g -CHW/PLLA nanocomposites were found to be 30.5 MPa, 1.4 GPa and 333.7 J/m 2, respectively, values that were significantly superior to those of the CHW/PLLA nanocomposites and neat PLLA. Cell culture results revealed that the g -CHW/PLLA nanocomposites were more suitable for cell adhesion and differentiation than those of the neat PLLA and CHW/PLLA nanocomposites.